“Impurity Profile Study of Aspirin in Bulk and Tablet Dosage Forms” (Journal of Pharmaceutical Negative Results, 2022)
Aspirin is one of the most frequently used and cheapest drugs in medicine. It belongs to the non-steroidal anti-inflammatory drugs with a wide range of pharmacological activities, including analgesic, antipyretic, and antiplatelet properties. Currently, it is accepted to prescribe a low dose of aspirin to pregnant women who are at high risk of preeclampsia (PE) because it reduces the onset of this complication. Drug produce degradation profiles essential to establish to monitor the stable formulation and provide appropriate drug shelf life valuation. Structural description of impurities and degeneracy production in bulk API has become integral part of pharmaceutical product development. The study of these minor leveled unidentified impurities and degradent are very challenging. Various regulatory bodies related International Council for Harmonisation, United States Food and Drug Administration.